The occurrence and physiology of Hyphopichia heimii, associated with beetle frass from Olea europaea subsp. cuspidata - Asmus, Justin Joseph (Stellenbosch : Stellenbosch University, 2020)
Thesis (MSc)--Stellenbosch University, 2020.